A multilingual key to the genera and subgenera of the subfamily Scarabaeinae of the New World (Coleoptera: Scarabaeidae) - Vaz de Mello, Fernando Z. (2011)
Presented is a multilingual (English, Portuguese, Spanish, Dutch and French) key to the 119 currently recognized genera and subgenera of scarabaeine dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) occurring in the New World. Also included are illustrations of representative species of all taxa included in the key as well as supplementary references to studies at the species level.